Environmental friendly products. - Ng, Valerie Siok Teng. (2008)
The study illustrates the factors affecting Singaporeans’ intention to purchase and their actual purchase of environmental friendly products as well as the comparison of Singaporeans with consumers from other countries in areas of their level of awareness on environmental friendly products and attitudes towards environmental friendly products.